IRE-1 endoribonuclease activity declines early in C. elegans adulthood and is not rescued by reduced reproduction - De-Souza, Evandro A.; Cummins, Nadia; Taylor, Rebecca C. (Frontiers in Aging, 2022)
The proteome of a cell helps to define its functional specialization. Most proteins must be translated and properly folded to ensure their biological function, but with aging, animals lose their ability to maintain a correctly folded proteome. This leads to the accumulation of protein aggregates, decreased stress resistance, and the onset of age-related disorders. The Unfolded Protein Response of the Endoplasmic Reticulum (UPR) is a central protein quality control mechanism, the function of which is known to decline with age. Here, we show that age-related UPR decline in Caenorhabditis elegans occurs at the onset of the reproductive period and is caused by a failure in IRE-1 endoribonuclease activities, affecting both the splicing of xbp-1 mRNA and RIDD (regulated Ire1 dependent decay) activity. Animals with a defect in germline development, previously shown to rescue the transcriptional activity of other stress responses during aging, do not show restored UPR activation with age. This underlines the mechanistic difference between age-associated loss of UPR activation and that of other stress responses in this system, and uncouples reproductive status from the activity of somatic maintenance pathways. These observations may aid in the development of strategies that aim to overcome the proteostasis decline observed with aging.